Oral Presentations 2015
DOI: 10.1136/jech-2015-206256.91
|View full text |Cite
|
Sign up to set email alerts
|

OP92 Temporal and weather effects on accelerometer-measured physical activity during school days among children

Abstract: BackgroundThough physical activity (PA) is beneficial for health, large proportions of children are inactive. Understanding how weather conditions influence PA will help inform effective PA strategies aimed at increasing PA during childhood. The aim of this study was to investigate temporal and seasonal variability in objective PA among school-aged children and its association with weather conditions.MethodsCross sectional data from 8–11 year old primary school children in Cork, Ireland. Triaxial accelerometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another issue to address is the possibility of presenting a magnified picture of the average physical activity level throughout the year, as this data material was collected only during the spring. Previous studies (8, 66, 67) have revealed seasonal variations in physical activity level, finding that 6–10 years-old children were more physically active during spring and summer. These differences were however not present among Norwegian and Danish youths from 14 to 16 years (8, 66).…”
Section: Discussionmentioning
confidence: 86%
“…Another issue to address is the possibility of presenting a magnified picture of the average physical activity level throughout the year, as this data material was collected only during the spring. Previous studies (8, 66, 67) have revealed seasonal variations in physical activity level, finding that 6–10 years-old children were more physically active during spring and summer. These differences were however not present among Norwegian and Danish youths from 14 to 16 years (8, 66).…”
Section: Discussionmentioning
confidence: 86%
“…Children’s physical activity levels during school hours vary according to the temperature and season [ 34 ]. This was highlighted in this study, where hot temperatures were frequently raised as a barrier to implementation.…”
Section: Discussionmentioning
confidence: 99%